حديث الأقرع والأبرص والأعمى دراسة تحليلية - Forat Mustafa Almazloum; Kabiru Goje (Universiti Sains Islam Malaysia, 2024)
Journal of Quran Sunnah Education & Special Needs, Volume 8 Issue 1 Page (125-138)